DIP-chip: Rapid and accurate determination of DNA-binding specificity - Liu, Xiao; Noll, David M.; Lieb, Jason D.; Clarke, Neil D. (Genome Research, 2005)
We have developed a new method for determining the DNA-binding specificity of proteins. In DIP-chip (DNA immunoprecipitation with microarray detection), protein·DNA complexes are isolated from an in vitro mixture of purified protein and naked genomic DNA. Whole-genome DNA microarrays are used to identify the protein-bound DNA fragments, and the sequence of the identified fragments is used to derive binding-site descriptions. Using objective criteria for assessing the accuracy of DNA-binding motifs, and using yeast Leu3p as a model, we demonstrate that motifs determined by DIP-chip are as effective at predicting the location of bound proteins in vivo as are motifs determined by conventional low-throughput in vitro methods.